ADAR1-dependent editing regulates human β cell transcriptome diversity during inflammation - Szymczak, Florian; Cohen-Fultheim, Roni; Thomaidou, Sofia; de Brachène, Alexandra Coomans; Castela, Angela; Colli, Maikel; Marchetti, Piero; Levanon, Erez; Eizirik, Decio; Zaldumbide, Arnaud (Frontiers in Endocrinology, 2022)
Enterovirus infection has long been suspected as a possible trigger for type 1 diabetes. Upon infection, viral double-stranded RNA (dsRNA) is recognized by membrane and cytosolic sensors that orchestrate the type I interferon signaling and the recruitment of innate immune cells to the pancreatic islets. In this context, adenosine deaminase acting on RNA 1 (ADAR1) editing plays an important role in dampening the immune response by inducing adenosine mispairing, destabilizing the RNA duplexes and thus preventing an excessive immune activation. Here, we evaluated the role of ADAR1 in human pancreatic  cells and determined the impact of type 1 diabetes pathophysiological environment on ADAR1-dependent RNA editing. We show that both IFNα and IFNɣ/IL1β stimulation promote ADAR1 expression and increase the A-to-I RNA editing of Alu-Containing mRNAs in EndoC-H1 cells as well as in primary human islets. We demonstrate that ADAR1 overexpression inhibits the type I interferon response signaling, while ADAR1 silencing potentiates IFNα effects. In addition, ADAR1 overexpression triggers the generation of alternative spliced RNAs, highlighting a novel role for ADAR1 as regulator of the  cell transcriptome under inflammatory conditions.